Almayer’s Folly: Conrad’s investigation into modern man’s unpromising fate - Koohestanian, Farhang; Omar, Noritah (Universiti Putra Malaysia Press, 2013)
Almayer’s Folly is Conrad’s initial step in his long journey to trace the soul of modern man, overshadowed by rapid developments in science and technology intensifying particularly from the second half of the nineteenth century. Despite its positive aspects, modernity left man in such an uncertain state about everything including his own identity that his destruction seemed and it may still seem unavoidable. Twentieth-century man, stripped of his cloak of faith, relied far too much on his conscious ego as the modern truth. However, he soon realised that he could not have been more wrong as the consequences were devastating. Conrad depicts such a dubious state in his works, and unlike many of his contemporary counterparts, he comes up with a possible solution that may function as a modern salvation. For the reader, Conrad’s works are a journey or a quest of Self-discovery through which his principal characters, like mythical heroes traverse ups and downs and at the end are either defeated (as in his earlier works) or return as conquerors (more obvious in his later works). Almayer’s Folly is his very first work and the first step in his journey of individuation and may be regarded as the thesis of his dialectical method, in which Conrad vividly explores and portrays the unpleasant aspects of modernity and the reasons why modern man fails to establish an individual self.